2019
DOI: 10.1002/npr2.12057
|View full text |Cite
|
Sign up to set email alerts
|

Blonanserin versus haloperidol in Japanese patients with schizophrenia: A phase 3, 8‐week, double‐blind, multicenter, randomized controlled study

Abstract: Objective This Japanese, multicenter, randomized, double‐blind trial, evaluating the efficacy and safety of blonanserin compared with haloperidol in patients with schizophrenia, was previously published by Murasaki in the Japanese language. In this article, we present the results of the trial based on full analysis dataset instead of per protocol dataset formerly reported and discuss the findings in light of the latest knowledge of pharmacological treatment for schizophrenia. Methods A total of 265 patients we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
29
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 17 publications
(31 citation statements)
references
References 24 publications
2
29
0
Order By: Relevance
“…Blonanserin was reportedly more effective to negative symptoms than haloperidol . The recent meta‐analysis indicated that blonanserin has potentially superior efficacy in negative symptoms to other SGAs .…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Blonanserin was reportedly more effective to negative symptoms than haloperidol . The recent meta‐analysis indicated that blonanserin has potentially superior efficacy in negative symptoms to other SGAs .…”
Section: Discussionmentioning
confidence: 99%
“…Due to its receptor‐binding profiles, blonanserin is expected to improve positive and negative symptoms, while suppressing extrapyramidal side effects that were a serious problem in FGAs. Previous reports on randomized controlled trials showed similar efficacy of blonanserin in various psychiatric symptoms in schizophrenia compared with haloperidol or risperidone …”
Section: Introductionmentioning
confidence: 88%
See 3 more Smart Citations